Data protection and privacy : data protection and democracy - Annual International Conference on Computers, Privacy, and Data Protection 2019 : Brussels, Belgium); Hallinan, Dara; Leenes, Ronald; Gutwirth, Serge; Hert, Paul de (Oxford : Hart, 2020)
"The subjects of this volume are more relevant than ever, especially in light of the raft of electoral scandals concerning voter profiling. This volume brings together papers that offer conceptual analyses, highlight issues, propose solutions, and discuss practices regarding privacy and data protection. It is one of the results of the twelfth annual International Conference on Computers, Privacy and Data Protection, CPDP 2019, held in Brussels in January 2019. The book explores the following topics: dataset nutrition labels, lifelogging and privacy by design, data protection iconography, the substance and essence of the right to data protection, public registers and data protection, modelling and verification in data protection impact assessments, examination scripts and data protection law in Cameroon, the protection of children's digital rights in the GDPR, and the concept of the scope of risk in the GDPR. This interdisciplinary book has been written at a time when the scale and impact of data processing on society - not only on individuals, but also on social systems - is becoming ever starker. It discusses open issues as well as daring and prospective approaches, and will serve as an insightful resource for readers with an interest in computers, privacy and data protection"--
1. The Dataset Nutrition Label: A Framework to Drive Higher Data Quality Standards Sarah Holland, Ahmed Hosny, Sarah Newman, Joshua Joseph and Kasia Chmielinski 2. A Right to a Rule: On the Substance and Essence of the Fundamental Right to Personal Data Protection Lorenzo Dalla Corte 3. What's in an Icon? Promises and Pitfalls of Data Protection Iconography Arianna Rossi and Monica Palmirani 4. 'We're All in Th is Together': Actors Cooperating in Enhancing Children's Rights in the Digital Environment after the GDPR Domenico Rosani 5. Risk to the 'Rights and Freedoms': A Legal Interpretation of the Scope of Risk under the GDPR Katerina Demetzou 6. Modelling and Verification in GDPR's Data Protection Impact Assessment: A Case Study on the AccuWeather/Reveal Mobile Case Wolfgang Schulz, Florian Wittner, Kai Bavendiek and Sibylle Schupp 7. In Search of Data Protection's Holy Grail: Applying Privacy by Design to Lifelogging Technologies Liane Colonna 8. Public Registers Caught between Open Government and Data Protection ? Personal Data, Principles of Proportionality and the Public Interest Geert Lokhorst and Mireille van Eechoud 9. Examination Scripts as Personal Data: The Right of Access as a Regulatory Tool against Teacher-Student Abuses in Cameroon Universities Rogers Alunge 10. The Proposed ePrivacy Regulation: The Commission's and the Parliament's Draft s at a Crossroads? Elena Gil Gonzl̀ez, Paul De Hert and Vagelis Papakonstantinou 11. CPDP: Closing Remarks Giovanni Buttarelli
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Data protection -- Law and legislation -- Congresses; Privacy, Right of -- Congresses; IT & Communications law; Electronic books